Cooling by sweeping: A new operation method to achieve ferroic refrigeration without fluids or thermally switchable components. (May 2019) - Silva, D.J.; Amaral, J.S.; Amaral, V.S.
Highlights: An operation mode for caloric refrigeration, "cooling by sweeping", is presented. Device heat flow is established by exploiting applied field dynamics. A simple magnetic refrigerator geometry is considered for validation. Using this method, no fluids or thermally switchable components are required. Abstract: So far, all ferroic-based refrigerator prototypes have relied either in fluids or thermally switchable components as main heat exchangers, which brings some issues in terms of their applicability, such as the use of pumps for moving the fluid and the availability of thermally switchable components. We show that such heat exchangers are not necessary if field dynamics are explored. By using the example of magnetocaloric refrigeration, we show numerically that the operation of a simple apparatus constituted only by a magnetocaloric material and a magnet sweeping at a given frequency results in refrigeration. With the optimization of the type of motion, resting times after the complete application and removal of the magnetic field and frequency, a temperature span of 0.87 K is reached, which represents ∼ 20% of the maximum adiabatic temperature span of the material used in modeling, gadolinium.